ANALISIS PERBEDAAN RETURN SAHAM SEBELUM DAN SESUDAH HARI LIBUR KEAGAMAAN SERTA HARI LIBUR NASIONAL (Studi Empiris pada Indeks Harga Saham Gabungan (IHSG) di Bursa Efek Indonesia Periode 2007-2011) - Latifah, Uli; Prasetiono, Prasetiono (Faculty of Economics and Business Diponegoro University, 2012)
This research aims to analyze the differences in stock returns before and after the religious holidays and national holidays in the Composite Stock Price Index in the Indonesia Stock Exchange 2007-2011 period. Formulation of the problem is first presented to analyze whether there are differences in stock returns before and after religious holiday; secondly, to analyze whether there are differences in stock returns before and after the national holiday ;third, to analyze whether there are differences in stock returns before religious holidays and before a national holiday; fourth, to analyze whether there are differences in stock returns after the religious holiday and after a national holiday. This research uses the Composite Stock Price Index in the Indonesia Stock Exchange from 2007 to 2011 as a sample. The variables used are the stock returns with stock returns one day before the religious holiday, stock returns one day after the religious holiday, stock returns one day before national holidays, and stock returns one day after a national holiday. The method of analysis used in this reserch were sample t-test. These results prove that there is no difference in stock returns before and after the religious holiday, there is no difference in stock returns before and after the national holiday, there isÂ no differences in stock returns before religious holidays and before national holiday, and there is no difference in stock returns after religious holidays and after a national holiday.